Investigating the Impact of Supply Chain Agility, Government Regulations and Supply Chain Efficiency on Business Performance: Mediating Role of Cost Leadership - Tawee Jamjumrus; Noppadol Sritragool (International Journal of Supply Chain Management, 2019)
This study focuses on the effect of supply chain agility, efficiency and government regulations on the business performance of firms. It also focuses on the adaptation abilities of firms because of changing environment effecting their supply chain performance through its cost leadership strategy. Survey approach in the form of questionnaires have been adopted to collect data from the manufacturing firms in Thailand. Purposive sampling technique is used to select sample. The constructs were sent through mails and direct contact with firms. Incomplete items were removed leaving the sample size of 272. The collected information is then analyzed by adopting SPSS and AMOS. This study clearly depicts that there exist a significant progressive association between SC agility and SC efficiency on the performance of firms in Thailand. It also generates that strict government regulations decreases the supply chain and business performance. Moreover, cost leadership strategy also played an imperative role and showed significance mediation relation between this emerging collaboration and relationship. This research provides theoretical and managerial implications. It is an additional count in the literature related to supply chain practices and regulations or guidelines affecting such performance. It also provide strategic techniques to align firms supply chain management practices with rapidly changing industrial policies. It is considered to be a new study as it helps firms integrated in supply chain practices to focus on their strategies and policies in order to attain competitive edge globally.